Tantangan Khawarij, Thalhah, dan Muawiyah di Masa Ali Bin Abi Thalib: Analisis Politik, Sejarah, dan Dampaknya terhadap Dinamika Kepemimpinan Islam Awal - Icksan Asry Fabanjo; Ansar Tohe (Al-Kindi, 2026)
This article comprehensively analyzes the political challenges faced by Ali bin Abi Talib during his tenure as the fourth caliph (35–40 AH/656–661 CE), focusing on three primary opposition groups: Talha bin Ubayd-Allah and Zubayr bin al-Awwam, Mu'awiyah bin Abi Sufyan, and the Kharijites. Employing a library research approach with a descriptive-analytical qualitative method—grounded in historical and Islamic political perspectives—this study examines the causes of conflict, evolving political dynamics, Ali’s leadership strategies, and their impact on governmental stability and Muslim unity. The findings reveal that the challenges Ali faced were multidimensional, encompassing demands for retribution (*qisas*) for Uthman’s death, the political ambitions of the Umayyad family, divergent religious interpretations, economic disparities, and issues regarding leadership legitimacy. The conflict with Talha and Zubayr during the Battle of the Camel reflects the tension between the demand for justice and political stability, while the conflict with Mu'awiyah during the Battle of Siffin and the *Tahkim* (arbitration) event represents the clash between religious idealism and pragmatic political realities. The emergence of the Kharijites as an extremist group illustrates how differences of opinion can give rise to radical theological-political fragmentation. The study concludes that Ali’s leadership strategy—which prioritized consultation and the upholding of truth—encountered structural obstacles due to a weak power base and strong, organized opposition. The relevance of the conflicts during Ali’s era to contemporary Islamic political dynamics lies in the importance of managing differences, upholding balanced justice, fostering inclusive leadership, and remaining vigilant against extremism and identity politics to preserve the unity of the *Ummah*.